Effect of conjugal bereavement on mortality of the bereaved spouse in participants of the Renfrew/Paisley Study - Hart, Carole L (BMJ Group, 2007)
OBJECTIVES: To investigate how loss of a spouse affects mortality risk in the bereaved partner. DESIGN AND SETTING: Prospective cohort study in Renfrew and Paisley in Scotland. PARTICIPANTS: 4395 married couples aged 45–64 years when the study was carried out between 1972 and 1976. METHODS: The date of bereavement for the bereaved spouse was the date of death of his or her spouse. Bereavement could occur at any time during the follow‐up period, so it was considered as a time‐dependent exposure variable and the Cox proportional hazards model for time‐dependent variables was used. The relative rate (RR) of mortality was calculated for bereaved versus non‐bereaved spouses and adjusted for confounding variables. MAIN OUTCOME MEASURES: Causes of death to 31 March 2004. RESULTS: Bereaved participants were at higher risk than non‐bereaved participants of dying from any cause (RR 1.27; 95% CI 1.2 to 1.35). These risks remained but were attenuated after adjustment for confounding variables. There were raised RRs for bereaved participants dying of cardiovascular disease, coronary heart disease, stroke, all cancer, lung cancer, smoking‐related cancer, and accidents or violence. After adjustment for confounding variables, RRs remained higher for bereaved participants for all these causes except for mortality from lung cancer. There was no strong statistical evidence that the increased risks of death associated with bereavement changed with time after bereavement. CONCLUSIONS: Conjugal bereavement, in addition to existing risk factors, is related to mortality risk for major causes of death.